Nepenthes Ethyl Acetate Extract Provides Oxidative Stress-Dependent Anti-Leukemia Effects - Wangta Liu; Li-Ching Lin; Pei-Ju Wang; Yan-Ning Chen; Sheng-Chieh Wang; Ya-Ting Chuang; I-Hsuan Tsai; Szu-Yin Yu; Fang-Rong Chang; Yuan-Bin Cheng; Li-Chen Huang; Ming-Yii Huang; et al. (MDPI AG, 2021)
Several kinds of solvents have been applied to Nepenthes extractions exhibiting antioxidant and anticancer effects. However, they were rarely investigated for Nepenthes ethyl acetate extract (EANT), especially leukemia cells. The purpose of the present study was to evaluate the antioxidant properties and explore the antiproliferation impact and mechanism of EANT in leukemia cells. Five standard assays demonstrated that EANT exhibits antioxidant capability. In the cell line model, EANT dose-responsively inhibited cell viabilities of three leukemia cell lines (HL-60, K-562, and MOLT-4) based on 24 h MTS assays, which were reverted by pretreating oxidative stress and apoptosis inhibitors (N-acetylcysteine and Z-VAD-FMK). Due to similar sensitivities among the three cell lines, leukemia HL-60 cells were chosen for exploring antiproliferation mechanisms. EANT caused subG1 and G1 cumulations, triggered annexin V-detected apoptosis, activated apoptotic caspase 3/7 activity, and induced poly ADP-ribose polymerase expression. Moreover, reactive oxygen species, mitochondrial superoxide, and mitochondrial membrane depolarization were generated by EANT, which was reverted by N-acetylcysteine. The antioxidant response to oxidative stress showed that EANT upregulated mRNA expressions for nuclear factor erythroid 2-like 2 (NFE2L2), catalase (CAT), thioredoxin (TXN), heme oxygenase 1 (HMOX1), and NAD(P)H quinone dehydrogenase 1 (NQO1) genes. Moreover, these oxidative stresses led to DNA damage (γH2AX and 8-hydroxy-2-deoxyguanosine) and were alleviated by N-acetylcysteine. Taken together, EANT demonstrated oxidative stress-dependent anti-leukemia ability to HL-60 cells associated with apoptosis and DNA damage.